2019
DOI: 10.1104/pp.18.01303
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Coupling of Vessel Cavitation and Discharge of Stored Xylem Water in a Tree Sapling

Abstract: Water discharge from stem internal storage compartments is thought to minimize the risk of vessel cavitation. Based on this concept, one would expect that water storage compartments involved in the buffering of xylem tensions empty before the onset of vessel cavitation under drought stress, and potentially refill after soil saturation. However, scant in vivo data exist that elucidate this localized spatiotemporal coupling. In this study on intact saplings of American chestnut (Castanea dentata), x-ray computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 29 publications
(41 reference statements)
5
37
0
Order By: Relevance
“…suggesting that water may be released from fibres in these species (as well as vessels, see 556 above). This is in agreement with microCT evidence of emptying fibres (and vessels) as 557 water potential decreases (Knipfer et al 2017(Knipfer et al , 2019). An interesting path forward would be to 558 measure the size of fibre lumina and taper, because these characteristics could have an 559 additional effect on capillary water release as capillary tension and lumen diameter are 560 negatively correlated (Tyree & Yang 1990;Hölttä et al 2009).…”
Section: Day Capacitance and Cumulative Water Release 498supporting
confidence: 86%
See 1 more Smart Citation
“…suggesting that water may be released from fibres in these species (as well as vessels, see 556 above). This is in agreement with microCT evidence of emptying fibres (and vessels) as 557 water potential decreases (Knipfer et al 2017(Knipfer et al , 2019). An interesting path forward would be to 558 measure the size of fibre lumina and taper, because these characteristics could have an 559 additional effect on capillary water release as capillary tension and lumen diameter are 560 negatively correlated (Tyree & Yang 1990;Hölttä et al 2009).…”
Section: Day Capacitance and Cumulative Water Release 498supporting
confidence: 86%
“…Given these knowledge gaps, it is surprising that parenchyma, the main living tissue 83 in wood commonly believed to have elastic cell walls, is often assumed the primary source of (fibres, vessels) via highly lignified middle lamella impeding parenchyma independent 95 volumetric changes. Moreover, recent microCT studies, suggest that water released from 96 cavitating fibres and vessels may contribute meaningfully to capacitance at moderate water 97 potentials (Knipfer et al 2017(Knipfer et al , 2019. 98…”
Section: Introductionmentioning
confidence: 99%
“…Further research in wood anatomy and tree water content regulation under drought stress (Knipfer et al, ; Martinez‐Vilalta et al, ) could help to more accurately discriminate how stem capacitive water sources are preferentially used during drought stress, and to better understand the underlying link between C S and the regulation of water potential and carbon and water exchange. More long‐term data on stem water pools, C S and allometric adjustments applying non‐destructive techniques across different species would be necessary to evaluate the generality of the pattern observed here and advance knowledge on hydraulic acclimation strategies across plant functional types.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of water released at this point largely depends on the amount and lumen size of embolized conduits. Recent studies performed in vivo using X‐ray microtomography question, however, whether this sequential release of capacitive water sources along the desorption curve, which has been derived from excised branches, can be extrapolated to living plants (Knipfer et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of storage pools in the xylem, however, is negligible compared to the flow rate during transpiration in many plants 44 , including first-year grapevine stems and thus is unlikely to shape pressure gradients within our model domain to any significant extent. Moreover, it has been shown that even storage pools theoretically available in the xylem can remain largely unused in vivo 45,46 , meaning that their effect on local pressure gradients is likely less pronounced than their total capacity suggests. Finally, while significant release of water from storage can temporarily affect transverse pressure gradient patterns, it is unclear why this mechanism should lead to a decreased overall contribution of widest vessels to flow.…”
Section: Resultsmentioning
confidence: 99%